Integrated hierarchical surface restructuring of assembled electrode arrays for next-generation neural interfaces - Alexander Blagojevic; Wesley Roser; Wesley Seche; Pouya Tavousi; Sina Shahbazmohamadi; Shahram Amini (PLoS ONE, 2026)
Neurostimulation devices rely on electrode arrays to deliver targeted electrical stimulation for modulating nerve activity. Enhancing stimulation specificity, device battery and energy efficiency, and device miniaturization requires low-profile electrodes with exceptional electrochemical performance. Hierarchical Surface Restructuring (HSR™), a femtosecond laser-based electrode surface treatment technology, enables these improvements by significantly increasing the electrochemically active surface area of the electrode contacts through the formation of highly textured, multi-scale architectures. Although HSR™ offers substantial potential to enable both high-performance electrodes and further miniaturization of electrode arrays, its broader adoption in medical device manufacturing has been limited by cost considerations and the inherent complexities of integrating new surface modification steps into established production workflows. This study investigates the feasibility of applying HSR™ technology to commercially available Pt-10Ir paddle-type electrode arrays and, for the first time, demonstrates that HSR™ can be implemented as a stand-alone, post-fabrication surface modification process that is compatible with existing device geometries and material constraints. This advancement represents a significant step toward broader adoption of HSR™ by medical device manufacturers and demonstrates its overall manufacturing viability. The process developed in this study circumvents key barriers to industrial implementation by enabling HSR™ to be seamlessly integrated into existing production lines as a post-fabrication surface modification step, thereby eliminating the need for major or costly process changes. The morphology, electrochemical performance, and processing efficiency of the restructured electrodes were systematically characterized. HSR™ enhanced key electrochemical metrics—including charge storage capacity, specific capacitance, and impedance—by up to two orders of magnitude, while maintaining short processing times and full compatibility with the device’s geometry and constituent materials. These findings demonstrate the potential for HSR™ to be seamlessly integrated into existing manufacturing workflows as a post-fabrication step, providing a scalable and cost-effective approach for enhancing the electrochemical performance of neurostimulation electrode arrays. Furthermore, in-operando CO 2 -snow-assisted processing was shown to be equally compatible with established production lines, improving electrode stability and surface cleanliness without necessitating any upstream process modifications.